Supporting mental health: pre-post four-week psychological capacity building program for Indian target sport athletes - Gill, Shivjot; Singh, Parwinder (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. Mental training, widely recognised in sports psychology, has not been fully utilised to address broader mental health concerns among athletes, especially in India. This study examines the Psychological Capacity Building Program (PCBP) for Indian shooters and archers, focusing on key psychological variables such as motivation, grit, emotions, and well-being. The four-phase program includes sports analyses, individual assessments, motivational tasks, a one-week psychoeducational phase on mental skills, and two weeks of applying these skills in the athlete’s daily training routines.Methods. Psychometric tools such as the Sports Motivation Scale-II (SMS-II), Mental Health Continuum-Short Form (MHC-SF), Sports Emotion Questionnaire (SEQ), and Grit Scale were used to measure pre- and post-intervention scores of 122 athletes, divided into experimental (n = 60) and control (n = 62) groups. Within-group and between-group analyses were conducted, along with effect size calculations.Results. The experimental group showed significant improvements in happiness (p < 0.001), emotional well-being (p = 0.017), intrinsic motivation (p = 0.006), and grit (p = 0.004), alongside reductions in dejection (p = 0.001) and non-regulation (p < 0.001). In contrast, the control group experienced increased anger (p = 0.005) but no other significant changes. Between-group comparisons revealed greater reductions in anxiety (p < 0.001) and significant improvements in happiness (p < 0.001), emotional well-being (p < 0.001), social well-being (p < 0.001), and grit (p = 0.004) in the experimental group.Conclusions. PCBP shows promise for enhancing the athlete’s mental health, but further research with larger samples is needed to confirm its effectiveness and long-term adaptability across diverse sports.
Keywords: well-being; sport; archery; mental health; motivation; shooting